Penerapan Hukum Lingkungan dalam Pengelolaan Sumber Daya Alam: Penelitian - Wilma Silalahi; Joe Aprella Indra (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
The management of natural resources in Indonesia faces significant challenges regarding the effectiveness of environmental law enforcement and the role of law enforcement agencies. This study examines the implementation of environmental regulations, including Law No. 32 of 2009 on Environmental Protection and Management, and legal mechanisms applied to ensure the sustainable use of natural resources. The results indicate that the effectiveness of environmental law is influenced by inter-agency coordination, the capacity of supervising officers, compliance of business actors, and public participation. Law enforcement institutions such as the Police, Prosecutor’s Office, Ministry of Environment and Forestry, and courts play a strategic role through administrative sanctions, criminal penalties, and technical supervision. Major challenges include overlapping authorities between central and regional governments, limited resources, and over-exploitation practices that harm the environment. The study concludes that the successful management of natural resources requires the integration of formal regulations, strict law enforcement mechanisms, and active public participation to achieve environmental sustainability.